2021
DOI: 10.5194/wes-6-1043-2021
|View full text |Cite
|
Sign up to set email alerts
|

Extreme wind shear events in US offshore wind energy areas and the role of induced stratification

Abstract: Abstract. As the offshore wind industry emerges on the US East Coast, a comprehensive understanding of the wind resource – particularly extreme events – is vital to the industry's success. Such understanding has been hindered by a lack of publicly available wind profile observations in offshore wind energy areas. However, the New York State Energy Research and Development Authority recently funded the deployment of two floating lidars within two current lease areas off the coast of New Jersey. These floating l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 48 publications
3
32
0
1
Order By: Relevance
“…We study 2020-05-15, a day in which the NYSERDA floating lidar [9] observed an LLJ in the New York Bight that persisted for approximately 9 hours, starting from 15:00 UTC. Selection of this case day was based on the jet-identification criteria of [18] and motivated by the excellent agreement between WRF mesoscale model predictions and the observations. Mesoscale data were provided by the same model setup as used by other researchers that recently studied the same offshore region [19].…”
Section: Validation Against Observation Datamentioning
confidence: 99%
“…We study 2020-05-15, a day in which the NYSERDA floating lidar [9] observed an LLJ in the New York Bight that persisted for approximately 9 hours, starting from 15:00 UTC. Selection of this case day was based on the jet-identification criteria of [18] and motivated by the excellent agreement between WRF mesoscale model predictions and the observations. Mesoscale data were provided by the same model setup as used by other researchers that recently studied the same offshore region [19].…”
Section: Validation Against Observation Datamentioning
confidence: 99%
“…Similarly, frictional decoupling can also occur when warmer air is advected over a cooler surface, typically during spring or early summer when the wind is directed from land towards a water surface and the water is still cold after the winter (e.g., Smedman et al, 1993;Smedman et al, 1997;Debnath et al, 2021) or during winter when air is advected over an ice sheet (Vihma and Brümmer, 2002). As a result of the uneven response to daytime warming of a land surface compared to the water surface, a sea-breeze circulation can form, and this alteration of the wind profile can in turn create an LLJ (e.g., Fisher, 1960; see also Aird et al, 2022).…”
Section: Formation Of Non-idealized Profilesmentioning
confidence: 99%
“…Similarly, frictional decoupling can also occur when warmer air is advected over a cooler surface, typically during spring or early summer when the wind is directed from land towards a water surface and the water is still cold after the winter (e.g. Smedman et al 1993, Smedman et al 1997and Debnath et al 2021 or during winter when air is advected over an ice sheet (Vihma and Brümmer, 2002). As an effect of the uneven response to daytime warming of a land surface compared to a water surface, a sea-breeze circulation can form, and this alteration of the wind profile can in turn create an LLJ (e.g., Fisher, 1960).…”
Section: Formation Of Non-normal Profilesmentioning
confidence: 99%